Estratégias eletrolíticas: controle do estresse térmico em ovinos - Catalano, Francisco Augusto Ricci [UNESP] (2014)
Heat stress is the imbalance that occurs in the animal organism in response to adverse weather conditions, triggering several metabolic disorders, physiological and productive animals. In order to control the physiological changes of the sheep to thermal stress, it was proposed to use appropriate levels of electrolyte and its appropriate proportion in the feed. Thus the present study aimed to evaluate the effect of changes in electrolyte balance of diets, based on changes in the balance sheet (BE) and electrolyte ratio (RE) as a way to control the physiological changes caused by thermal stress in sheep. Therefore, we considered the physiological parameters of 12 lanados lambs were assigned to a completely randomized experimental design, in incomplete factorial arrangement 3x3 with five diets, resulting from combinations of BE 0, 50 and 100 and RE 5: 1, 10: 1 to 15: 1. The physiological parameters were evaluated in three distinct periods, two with average temperatures of 28 ° C, with an intermediate period with temperatures ranging between 35 and 37 ° C. The results were submitted to analysis of variance and regression analysis later. The physiological parameters heart rates, respiratory, rectal mucosal temperature, eyeball, armpit and ruminal movements were sensitive to the supplementation levels of BE and RE. The results indicated that the groups with lower BE RE 50 and 8 to 14 were superior. Thus we conclude that the optimum use of electrolyte balance in sheep was able to modulate physiological responses of these animals mitigating the effects of heat stress